HUBUNGAN RIWAYAT HIPERTENSI DAN PARITAS DENGAN ASFIKSIA NEONATORUM PADA IBU BERSALIN PREEKLAMPSIA BERAT - Dyah Muliawati; Endang Sutisna; uki retno (Sekolah Tinggi Ilmu Kesehatan Madani Yogyakarta, 2016)
Asphyxia neonatorum is a condition when a newborn baby experiencing spontaneous and regular breathing failure. It is the main cause of newborn death in the developing countries with rate of 21.1%, ones of the maternal factors that contribute to a.n are preeclampsia and eclampsia. The purpose of the research is to analyze the relationships of hypertension history and parity with asphyxia neonatorum case on mothers with severe preeclampsia. The subjects are 40 babies with and 40 babies without asphyxia case born by mothers with severe preeclampsia. The research type is quantitative research, analytical observation method, design case-control, and a retrospective approach with study of documentations in the year 2014 in the Provincial Hospital of Panembahan Senopati Bantul. The analysis methods are the bivariat analysis with Chi-Square test, and multivariate analysis with logistic regression test. The mother with a history of hypertension risk 11.9 times greater than without a history of hypertension (OR = 11.9; CI 95% = 1.92 - 73.79; p = 0.008). The mother was birthing the risk of primipara babies with asphyxia is 3.43 times greater than that of multipara (OR = 3.43; CI 95% = 1.08 - 10.88; p = 0.036). There is a positive relationship and statistically significant between hypertension history and parity with the risks of giving birth for babies with asphyxia case.